How plant–soil feedbacks influence the next generation of plants. Issue 1 (25th August 2020) - De Long, Jonathan R.; Heinen, Robin; Jongen, Renske; Hannula, S. Emilia; Huberty, Martine; Kielak, Anna M.; Steinauer, Katja; Bezemer, T. Martijn
Abstract: In response to environmental conditions, plants can alter the performance of the next generation through maternal effects. Since plant–soil feedbacks (PSFs) influence soil conditions, PSFs likely create such intergenerational effects. We grew monocultures of three grass and three forb species in outdoor mesocosms. We then grew one of the six species, Hypochaeris radicata, in the conditioned soils and collected their seeds. We measured seed weight, carbon and nitrogen concentration, germination and seedling performance when grown on a common soil. We did not detect functional group intergenerational effects, but soils conditioned by different plant species affected H. radicata seed C to N ratios. There was a relationship between parent biomass in the differently conditioned soils and the germination rates of the offspring. However, these effects did not change offspring performance on a common soil. Our findings show that PSF effects changed seed quality and initial performance in a common grassland forb. We discuss the implications of our findings for multi‐generational plant–soil interactions, and highlight the need to further explore how PSF effects shape plant community dynamics over different generations and across a broad range of species and functional groups. Abstract : We show that plant‐soil feedback effects experienced by the parent plant resulted in changes in seed quality and initial performance of a common grassland forb.